Análise exploratória da política monetária e sua relação com a atração de investimentos do mercado de capitais em infraestrutura - Lima, Eduarda Marielle de (Universidade Federal de São Carlos, 2023)
Considering that the infrastructure sector is an important component for the growth and development of a country and that investments in this area tend to actively benefit the population in various ways, it becomes substantial to analyze how the evolution of these investments has occurred over time to understand the prospects of this market in Brazil. In this way, the objective of this study is to conduct an exploratory analysis of the relationship between the current monetary policy in Brazil and the evolution of investment raising, through the capital market, for the infrastructure sector, with a focus on incentivized debentures, in order to understand how such policy could influence this sector, whether it can or cannot mitigate the bottlenecks present in it. To achieve this, the period from 2013 to 2022 is used throughout the work to perform a descriptive data analysis with the support of tools such as graphs and tables, utilizing the available information on fundraising, through the capital market, for infrastructure investments. As the main results obtained, it has been evident the relevant role of the interest rate, the primary instrument of monetary policy, in fundraising through incentivized debentures for investments in the infrastructure sector, and it has also been observed that the attraction of such investments, through the capital market, has been increasingly significant.
Exploratory analysis of monetary policy and its relationship with attracting investments in infrastructure capital markets
Keywords: Política Monetária; Infraestrutura; Mercado de Capitais; Financiamento; Debênture; Monetary Policy; Infrastructure; Capital Markets; Financing; Debenture; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::TEORIA MONETARIA E FINANCEIRA